Optimalization of afterburner channel in biomass boiler using CFD analysis - Pospíšil, Jiří; Lisý, Martin; Špiláček, Michal (Czech Technical University in Prague, 2016)
This contribution presents the results of parametrical studies focused on the mixing process in a small rectangular duct within a biomass boiler. The first study investigates the influence of a local narrowing located in the central part of the duct. This narrowing works as an orifice with very simple rectangular geometry. Four different free cross sections of the orifice were considered in the center of the duct, namely 100 %, 70 %, 50 %, 30 % of free cross section area in the duct. The second study is focused on the investigation of the influence of secondary air distribution pipe diameter on the mixing process in a flue gas duct without a narrowing.

This contribution presents the results of parametrical studies focused on the mixing process in a small rectangular duct within a biomass boiler. The first study investigates the influence of a local narrowing located in the central part of the duct. This narrowing works as an orifice with very simple rectangular geometry. Four different free cross sections of the orifice were considered in the center of the duct, namely 100 %, 70 %, 50 %, 30 % of free cross section area in the duct. The second study is focused on the investigation of the influence of secondary air distribution pipe diameter on the mixing process in a flue gas duct without a narrowing.
Optimalization of afterburner channel in biomass boiler using CFD analysis
Keywords: CFD analysis; flue-gas; mixing; emissions; CFD analysis; flue-gas; mixing; emissions